2021
DOI: 10.3390/ijerph18147457
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Physical Education Teachers’ (De-)Motivating Style, Students’ Motivation, and Students’ Physical Activity: A Multilevel Approach

Abstract: Research suggests that physical education (PE) teachers can play a crucial role in the promotion of students’ physical activity. Grounded in Self-Determination Theory, this study investigated how students’ perceptions of PE teachers (de-)motivating style relate to students’ device-based physical activity levels during PE. Moreover, it was examined whether students’ motivation plays an intervening role in this relation and whether students’ physical activity differs according to their gender and lesson topic. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…Limitations and reflections. Previous literature indicates that teachers motivating styles have implications for future students' PA both in and out of school (Ng et al, 2012;Teixeira et al, 2012;Van Doren et al, 2021). However, it is important to note that autonomous motivation toward activities in PE predicts autonomous motivation toward PA outside of school which associates with self-reported PA, but not objectively measured PA (Hagger and Chatzisarantis, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Limitations and reflections. Previous literature indicates that teachers motivating styles have implications for future students' PA both in and out of school (Ng et al, 2012;Teixeira et al, 2012;Van Doren et al, 2021). However, it is important to note that autonomous motivation toward activities in PE predicts autonomous motivation toward PA outside of school which associates with self-reported PA, but not objectively measured PA (Hagger and Chatzisarantis, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…ompelling evidence suggests that teachers' interaction style influences students' motivation, well-being, and engagement in school (McQuillin and Lyons, 2016;Reich et al, 2015), and can also increase their physical activity (PA) (Ng et al, 2012;Teixeira et al, 2012;Van Doren et al, 2021). However, despite proven improvements in interaction styles after motivational interaction training, most trainees fail to achieve the desired skill levels or do not put the skills into practice (de Roten et al, 2013;Hall et al, 2016;Madson et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, beyond teaching style, previous studies have provided evidence to support the influence of teacher behavior on students' MVPA levels. More precisely, students who perceive their teachers as more controlling spend less time in MVPA (Van Doren et al, 2021). Moreover, the more supportive and structuring teachers are, the more students engage in MVPA (Escriva-Boulley et al, 2018).…”
Section: Mvpa Scores and The Jigsaw Methodsmentioning
confidence: 99%
“…Researches reveal that the time students spend in MVPA does not meet the US Center for Disease Control and Prevention or United Kingdom Associations for PE recommendation of 50% in PE classes in elementary and secondary schools ( Hollis et al, 2015 , 2017 ). Some studies have shown that promotion of pupils’ physical exercise and motivation is substantially aided by PE teachers ( Moreno-Murcia et al, 2018 ; Emeljanovas et al, 2020 ; Van Doren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%